CRISPR/Cas9-Induced Disruption of Paraflagellar Rod Protein 1 and 2 Genes in Trypanosoma cruzi Reveals Their Role in Flagellar Attachment - Noelia Lander (American Society for Microbiology, 2015)
ABSTRACT Trypanosoma cruzi is the etiologic agent of Chagas disease, and current methods for its genetic manipulation have been highly inefficient. We report here the use of the CRISPR (clustered regularly interspaced short palindromic repeats)/Cas9 (CRISPR-associated gene 9) system for disrupting genes in the parasite by three different strategies. The utility of the method was established by silencing genes encoding the GP72 protein, which is required for flagellar attachment, and paraflagellar rod proteins 1 and 2 (PFR1, PFR2), key components of the parasite flagellum. We used either vectors containing single guide RNA (sgRNA) and Cas9, separately or together, or one vector containing sgRNA and Cas9 plus donor DNA for homologous recombination to rapidly generate mutant cell lines in which the PFR1, PFR2, and GP72 genes have been disrupted. We demonstrate that genome editing of these endogenous genes in T. cruzi is successful without detectable toxicity of Cas9. Our results indicate that PFR1, PFR2, and GP72 contribute to flagellar attachment to the cell body and motility of the parasites. Therefore, CRISPR/Cas9 allows efficient gene disruption in an almost genetically intractable parasite and suggest that this method will improve the functional analyses of its genome. IMPORTANCE Trypanosoma cruzi is the agent of Chagas disease, which affects millions of people worldwide. Vaccines to prevent this disease are not available, and drug treatments are not completely effective. The study of the biology of this parasite through genetic approaches will make possible the development of new preventive or treatment options. Previous attempts to use the CRISPR/Cas9 in T. cruzi found a detectable but low frequency of Cas9-facilitated homologous recombination and fluorescent marker swap between exogenous genes, while Cas9 was toxic to the cells. In this report, we describe new approaches that generate complete disruption of an endogenous gene without toxicity to the parasites and establish the relevance of several proteins for flagellar attachment and motility.